2017
DOI: 10.1002/bies.201700051
|View full text |Cite
|
Sign up to set email alerts
|

ZC3H12A/MCPIP1/Regnase‐1‐related endonucleases: An evolutionary perspective on molecular mechanisms and biological functions

Abstract: The mammalian Zc3h12a/MCPIP1/Regnase-1, an extensively studied regulator of inflammatory response, is the founding member of a ribonuclease family, which includes proteins related by the presence of the so-called Zc3h12a-like NYN domain. Recently, several related proteins have been described in Caenorhabditis elegans, allowing comparative evaluation of molecular functions and biological roles of these ribonucleases. We discuss the structural features of these proteins, which endow some members with ribonucleas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…In particular, our analysis suggested a new role for ZC3H12, BOLL, and DAZL proteins in regulating alternative splicing and for MEX3B in binding to type I interferonregulated genes. In particular, the binding of the antiviral cytoplasmic ZC3H12 proteins (Lin et al 2013;Habacher and Ciosk 2017) to splice junctions may have a role in their antiviral activity, as endogenous cytoplasmic mRNAs are depleted of splice donor sequences. As a large number of novel motifs were generated in the study, we expect that many other RBPs will have specific roles in particular biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, our analysis suggested a new role for ZC3H12, BOLL, and DAZL proteins in regulating alternative splicing and for MEX3B in binding to type I interferonregulated genes. In particular, the binding of the antiviral cytoplasmic ZC3H12 proteins (Lin et al 2013;Habacher and Ciosk 2017) to splice junctions may have a role in their antiviral activity, as endogenous cytoplasmic mRNAs are depleted of splice donor sequences. As a large number of novel motifs were generated in the study, we expect that many other RBPs will have specific roles in particular biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that Regnase-1 plays a broader role in the regulation of RNA beyond immune cells (Skalniak et al, 2014; Boratyn et al, 2016, 2017; Lu et al, 2016). However, phenotypic manifestations clearly show that a major, if not the primary, role of Regnase-1 is within the immune system: namely, preventing autoimmunity and ensuring pathogen defense (Iwasaki et al, 2011; Uehata et al, 2013; Mino and Takeuchi, 2015; Habacher and Ciosk, 2017). Molecular insights have revealed that Regnase-1 is an essential RNase in macrophages and in T cells, where it degrades mRNAs and viral RNAs in the cytoplasm and in foci (called P or GW bodies), which contain other mRNA regulatory factors and mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, our analysis suggested a new role for ZC3H12, BOLL and DAZL proteins in 506 regulating alternative splicing, and MEX3B in binding to type I interferon-regulated genes. In 507 particular, the binding of the anti-viral cytoplasmic ZC3H12 proteins (Lin et al 2013;Habacher and 508 Ciosk 2017) to splice junctions may have a role in their anti-viral activity, as endogenous cytoplasmic 509 mRNAs are depleted of splice donor sequences. As a large number of novel motifs were generated in 510 the study, we expect that many other RBPs will have specific roles in particular biological functions.…”
mentioning
confidence: 99%